Perkembangan Personality Sosial Usia Bayi Dan Toddler - Lisa Yunita; Dadan Surayana (Jurnal Family Education, 2021)
Toddlers are an age that is susceptible to developmental problems. An important period in the process of child development is the first five years which is the golden period of an individual's life or known as the golden period. Growth and development in children occurs throughout life which consists of several stages, one of which is the toddler period. Toddler period is in the range from childhood starting to walk alone until they walk and run easily, which is approaching the age of 12 to 36 months. This study aims to analyze the development of social personality in infants and toddlers. The method used in this research is a qualitative method using library research methods. Library research is research conducted using library materials, either in the form of books, notes or other reference sources. The results of the study showed that the development of social personality in infants in general is usually the first experience of socialization for babies with their mothers. At the age of 2 months (social period), infants are responsive to humans and non-humans. At 6 months, social smiles begin to appear, at 9-13 months, babies try to touch other babies' clothes, faces, hair, and imitate their behavior and voice. At the age of 16-18 months, babies begin to show negativism. Ages 18-24 months, babies are interested in playing with other babies and use play materials to form social relationships with them. Age 22-24 months, babies want to cooperate in a number of routine activities, such as bathing, eating, dressing